Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
algebra trouble. help?
i need a little help with this problem. please explain how i should go about doing it
if r does not equal s and r(x+s)=sx-t, then x=?
thanksss :)
thanks guys, those seem right to me, but the answer choices are:
a) (rs+t)/(s-r)
b) (rs+t)/(s+r)
c) (s+t)/(s-r)
d) (s+t)/(s+r)
e) (s-t)/(s-r)
:/
3 Answers
- nkpLv 51 decade agoFavorite Answer
r(x+s)=sx-t
==> rx + rs = sx - t
==> rx - sx = -rs - t
==> x(r - s) = -rs - t
==> x = (-rs - t)/(r - s)
- Anonymous1 decade ago
x= - rs+t/r-s the negative sign is in front of the fraction
t= -r(s+x)+sx
r= -sx+t/s+x the negative sign is in front of the s on the top of the equation not that it matters.
s= - rx+t/r-x
Source(s): Microsoft Math - ?Lv 41 decade ago
Just multiply everything out and then group the terms with "x" on one side of the eqn. Then divide out by the coefficient to get everything in terms of x. You'll get this:
x = (-t-rs)/(r-s)